Vaccination, Fear and Historical Relevance - Boddice, Rob (History compass, 2016)
Fears about vaccination are tenacious, despite an overwhelming weight of evidence in favour of immunisation and despite the potentially dangerous consequences of falling rates of immunity against once common diseases. Drawing on recent developments in the history of emotions and an extensive historiography on the history of vaccination, this article argues that fear of vaccination has become culturally idiomatic and highly resistant to fact-based education campaigns. A role is envisaged for historians to present, in accessible media, narratives of successful public-health campaigns and, at the same time, to demonstrate the contextual underpinnings of social fear in order to allay such fears in the present.